1994
DOI: 10.1007/bf00192562
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and pharmacokinetics of prostaglandin E1 administered by intravenous infusion in human subjects

Abstract: In a single-blind, randomized, two-way cross-over study with 12 healthy male volunteers, 60 micrograms of prostaglandin E1 (PGE1) or placebo was administered by intravenous infusion during a 120-min period. PGE1, 13,14-dihydro-PGE1 (PGE0) and 15-keto-PGE0 plasma concentrations were measured by a highly specific and sensitive GC-MS/MS method. Endogenous PGE1 plasma concentrations ranged between 1.2 and 1.8 pg.ml-1. Endogenous PGE0 and 15-keto-PGE0 plasma concentrations varied from 0.8 to 1.3 pg.ml-1 and from 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 9 publications
(11 reference statements)
2
23
1
Order By: Relevance
“…The rapid increase of plasma concentrations during infusion and the rapid fall post infusion corresponds with the published short terminal half-lives [7,11].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The rapid increase of plasma concentrations during infusion and the rapid fall post infusion corresponds with the published short terminal half-lives [7,11].…”
Section: Discussionsupporting
confidence: 52%
“…administration of a single dose of PGE, to healthy volunteers [6,7]. The aim of the present study was [1].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical use of these agents is predicated on certain assumptions about their pharmacokinetics, yet with few exceptions (69) detailed information about the clearance and metabolism of these agents in humans is lacking. Only recently, for example, was exogenous PGE 1 shown to be rapidly converted to circulating 13,14-dihydro-PGE 1 and 15-keto-PGE 1 in humans (70,71). The role of hPGT, if any, in the clearance from the circulation of medicinal PGs can now be approached experimentally by expressing the transporter in vitro and evaluating its interactions with these agents.…”
Section: Discussionmentioning
confidence: 99%
“…Cawello et al reported that the plasma elimination of PGE 1 exhibited two phases, that is, their half-lives were 0.2 min and 8.2 min for the a-phase and the b-phase, respectively, in human subjects. 23) However, by using the estimated parameters, the plasma concentration of PGE 1 in the newborn rats was predicted to decline mono-exponentially, and the biological half-life was estimated to be 3 min. Thus, we suggest that the approximate plasma elimination kinetics of PGE 1 can be simply presented by a 1-compartment model in this PRK modeling.…”
Section: Discussionmentioning
confidence: 99%